New Mobilities in Rural Spaces of the Andean Araucanía (Revista LIDER, 2018)
The objective of this study is to characterize the mobility process and to investigate the motivations of the migrants who come to inhabit the communes of Pucón and Melipeuco, located both in the Andean Araucanía in the south of Chile. Through the analysis of in-depth interviews conducted during 2015 and 2017, it was possible to build categories of migrants based on their main motivations. The results show a process that is generating changes in the traditional ways of inhabiting and conceiving rural spaces .